Early Hispanic Curse Tablets: Greek, Latin – and Iberian? - Marco Simón, Francisco (Religion in the Roman empire, 2019)
To date, thirteen curse tablets from the area of modern Spain have been published that can (roughly) be dated prior to the Augustan period, which is early in comparison to other similar texts in the Latin West. The two earliest examples are written in Greek, followed after a sizeable chronological gap by those in Latin. However, we also know of more than 100 texts written on lead in the Iberian language, with the earliest coming from the same period as the Greek examples. The funerary context of a handful of these tablets, as well as their apparent contents, such as lists of names, suggests that they might also be magico-religious texts, comparable to, say, the Oscan curse tablets in southern Italy. The texts in Latin, on the other hand, seem to be largely independent from these earlier efforts, suggesting a close dependence upon Italian models.